Rapid Detection of Aluminium and Iron Impurities in Lithium Carbonate Using Water-Soluble Fluorescent Probes - Hong-Mei Wu; Huai-Gang Cheng; Zi-Wen Zhu; Li Cui (Molecules)
The real-time measurement of the content of impurities such as iron and aluminium ions is one of the keys to quality evaluation in the production process of high-purity lithium carbonate; however, impurity detection has been a time-consuming process for many years, which limits the optimisation of the production of high-purity lithium carbonate. In this context, this work explores the possibility of using water-soluble fluorescent probes for the rapid detection of impurity ions. Salicylaldehyde was modified with the hydrophilic group dl-alanine to synthesise a water-soluble Al3+ fluorescent probe (Probe A). Moreover, a water-soluble Fe3+ fluorescent probe (Probe B) was synthesised from coumarin-3-carboxylic acid and 3-hydroxyaminomethane. Probe A and Probe B exhibited good stability in the pH range of 4–9 in aqueous solutions, high sensitivity, as well as high selectivity for Al3+ and Fe3+; the detection limits for Al3+ and Fe3+ were 1.180 and 1.683 μmol/L, whereas the response times for Al3+ and Fe3+ were as low as 10 and 30 s, respectively. Electrostatic potential (ESP) analysis and density functional theory calculations identified the binding sites and fluorescence recognition mechanism; theoretical calculations showed that the enhanced fluorescence emission of Probe A when detecting Al3+ was due to the excited intramolecular proton transfer (ESIPT) effect, whereas the fluorescence quenching of Probe B when detecting Fe3+ was due to the electrons turning off fluorescence when binding through the photoelectron transfer (PET) mechanism.